Successful Management of a Gastric Sleeve Leak with an Endoscopic Stent - Albin Abraham; Kaleem Rizvon; Jaspreet Singh; Ghulam Siddiqui; Apsara Prasad; Sadat Rashid; Magdalene Vardaros; Vikas Garg; Krishnaiyer Subramani; Paul Mustacchia (Case Reports in Gastrointestinal Medicine)
Laparoscopic sleeve gastrectomy has been a recently developed technique for treating morbid obesity. Gagner and Patterson performed the first laparoscopic sleeve gastrectomy as part of a duodenal switch procedure at Mount Sinai Hospital in New York in 1999. Since then many surgeons and institutions have adopted this technique. One of the most dreaded complications of sleeve gastrectomy is a leak along the staple line. We present the case of a 23-year-old female with gastric sleeve leak managed successfully with a fully covered wall flex stent. Our aim is to examine the incidence, causes, classification, and presentation of gastric sleeve leaks and to evaluate the use of endoscopic stents in its management.